Vibration and Damping Analysis of a Multilayered Composite Plate with a Viscoelastic Midlayer - Haochuan Wan; Yinong Li; Ling Zheng (Shock and Vibration)
Based on the theory of Donnell and Kirchhoff hypothesis and by using the complex constant model of viscoelastic materials, the vibration equations of five-layered constrained damping plate are established. The transfer matrix method (TMM) is improved and used to solve equations. The improved TMM is more effective to solve complex structural vibration. The influence of layer numbers, thickness of each layer, and arrangement of materials on vibration behavior are discussed. It is proved that multilayered plates can more effectively reduce natural frequency and obtain higher structural loss factor. The loss factor increases with the number of whole layers. Symmetrical structure can obtain higher structural loss factor than one-direction structure. Uniform arrangement of viscoelastic materials and constrained materials can obtain higher structural loss factor than nonuniform arrangement. There is different optimum frequency with different material thickness, and the optimum frequency is not dependent from layer numbers.